FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP MOTIVASI BELAJAR MAHASISWA DI STMIK STIKOM BALI - I Gusti Ngurah Satria Wijaya (Jurnal Santiaji Pendidikan (JSP), 2018)
In teaching and learning activities the role of motivation is very necessary. The low motivation of student learning is often thought to be the cause of the low quality of graduates of a college. This causes in some private universities, learning motivation factors get special attention. Based on the above background, the authors conducted a study that aims to examine the factors that affect student learning motivation in STIMIK Stikom Bali. The data used in this study is the primary data derived from the filling questionnaire from STIMIK STIKOM Bali students as many as 50 samples. The analysis technique used in this research is multiple linear regression where the independent variable is intrinsic factor (in student) and extrinsic factor (quality of lecturer, parent, lecture material, lecture method, library, lecture room and laboratory). The result of this research is intrinsic factor, lecturer quality, lecture method, lecture material, parent, rehabilitation / laboratory space, and library simultaneously have a significant influence on student learning motivation. And partially, intrinsic factor, lecturer quality, lecture method, lecture material, parent, lecture / laboratory space, and library show a positive relationship to the dependent variable that is student's learning motivation. The results of this study in the future can provide evaluation results for the management of STMIK STIKOM Bali management about factors that affect student learning motivation.